De Novo Histoid Leprosy in an Elderly: A Case Report and Review of the Literature. (5th November 2012) - Dimri, Deepak; Sethi, Bhawna; Kumar, Yogesh
Abstract : Histoid leprosy, an uncommon variant of lepromatous leprosy, develops usually as relapse in lepromatous patients who are on dapsone monotherapy, but uncommonly arises de novo . This rare form of the disease, with unique clinical and histopathological features, may pose a diagnostic challenge even to astute clinicians. We report the case that occurred de novo in an elderly who presented with small to large lesions all over the body. A fresh focus on histoid leprosy is the primary objective of this paper, especially in the context of the postglobal leprosy elimination era.